Introduction and establishment of Microplitis croceipes a larval parasitoid of heliothis in North Island pine forests - Herman, T.J.B.; Davidson, M.M (New Zealand Plant Protection, 2000)
Heliothis (Helicoverpa armigera) is a periodic pest of young pine trees (Pinus radiata) In response to a recent outbreak of this pest Microplitis croceipes a parasitoid of heliothis larvae was introduced into forests of the North Island volcanic plateau to augment biological control of heliothis A total of 13600 M croceipes pupae were released at monthly intervals over three seasons (199598) Successful overwintering of M croceipes populations confirmed establishment in the forests Mean monthly parasitism reached 107 in the third season Surveys at points radiating out from the release sites indicated that M croceipes was spreading at approximately 1 km per year